A New Concept in Peripheral Nerve Repair: Incorporating the Tunica Adventitia - Zuhour, Moath; İnce, Bilsev; Oltulu, Pembe; Gök, Orhan; Tekecik, Zülal (Journal of Reconstructive Microsurgery, 2024)
Pedicled, prefabricated, and free nerve flaps have several drawbacks, such as requiring microsurgical anastomosis, the need for secondary operations and the risk of developing thrombosis. In this study, we aimed to vascularize the repaired nerve in a single session by establishing a connection between the epineurium of the repaired median nerve and the tunica adventitia of the brachial artery.The technique was performed on the median nerves of a total of 42 rats over 13 weeks. While group 1 didn't receive any intervention, the following three groups (2, 3, and 4) received classic treatments (coaptation, graft, and vein conduit). In addition to classic treatments, the other three groups (5, 6, and 7) were vascularized by attaching the adventitia of the brachial artery to the repaired nerves. Nerve regeneration was evaluated using functional tests, immunohistochemical analysis, and electron microscope.The vascularized groups (5, 6, and 7) showed earlier functional recovery (p < 0.05). Vascularization reduced inflammation in the coaptation group, reduced fibrosis and degeneration in the nerve graft group, and reduced fibrosis, degeneration and disorganization while increased the number of passing fibers and myelination in the vein conduit group (p < 0.05). Vascularization provided superior ultrastructural findings. Microscopic analysis revealed a novel finding of “zone of neurovascular interaction” between the adventitia and the regenerating nerve.Vascularizing the repaired nerves with this new technique provided faster functional and better histological healing. Unlike classic vascularization techniques, this method does not require microsurgical anastomosis, does not carry the risk of thrombosis, and does not necessitate secondary operations. The “zone of neurovascular interaction” identified in this study revealed regenerating axon clusters alongside newly developed blood vessels. This important finding highlights a potential role of the tunica adventitia in nerve regeneration.
Keywords: adventitia; functional recovery; neovasculogenesis; nerve repair; vascularization